2019
DOI: 10.1080/16878507.2019.1655864
|View full text |Cite
|
Sign up to set email alerts
|

Radiological characteristics of glioblastoma multiforme using CT and MRI examination

Abstract: The purpose of this study was to describe, analyze and characterize computed tomography (CT) and magnetic resonance imaging (MRI) scan of glioblastoma multiforme (GBM) patients. One hundred and three clinically definite GBM patient information, CT and MRI images along with clinical records and demographic data were retrospectively collected from the radiology information system (RIS) database of the Radiology and Medical Imaging Department of King Fahd Medical City between January 2012 to March 2019. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
14
2
Order By: Relevance
“…Regarding the tumor localization, Flores in a cohort of 44 patients, including only cases of GBM according to the WHO classification from 2021 and very close to our demographic characteristics, found that the majority of tumors (59.1%) are located in the right cerebral hemisphere, and the most common localization relative to the lobe is the frontal (29.5%), followed by temporal and parietal with 25%, and the rarest localization in the occipital lobe [ 22 ]. In another study, similar in volume and gender distribution but with a significantly lower mean age (49.05 years), Abd-Elghany found that again the most common site of GBM was in the frontal lobe, followed by the temporal, parietal, occipital lobes, and most rarely-subtentorial [ 23 ]. Despite the differences in localization between the three cohorts, the most common localization is temporal, followed by parietal, frontal, and occipital, underlining the diffuse origin of the tumor from different brain structures.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the tumor localization, Flores in a cohort of 44 patients, including only cases of GBM according to the WHO classification from 2021 and very close to our demographic characteristics, found that the majority of tumors (59.1%) are located in the right cerebral hemisphere, and the most common localization relative to the lobe is the frontal (29.5%), followed by temporal and parietal with 25%, and the rarest localization in the occipital lobe [ 22 ]. In another study, similar in volume and gender distribution but with a significantly lower mean age (49.05 years), Abd-Elghany found that again the most common site of GBM was in the frontal lobe, followed by the temporal, parietal, occipital lobes, and most rarely-subtentorial [ 23 ]. Despite the differences in localization between the three cohorts, the most common localization is temporal, followed by parietal, frontal, and occipital, underlining the diffuse origin of the tumor from different brain structures.…”
Section: Discussionmentioning
confidence: 99%
“…Peritumoral brain edema is frequently seen in GB patients and can be visualized on MRI as a region of increased T2 signal intensity at the tumor margin. However, there is no consensus for the measurement or classification of peritumoral edema on MRI, and the appearance of edema and tumor mass on MRI is variable [21,22]. Laboratory animal imaging requires a higher field strength, in the range of 4.7-11.7 T (most commonly 7 T), compared to the standard clinical range of 1.5-3 T to obtain a better spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…3,8 GBM usually occurs after the age of 40 years. 5,7,9,10 This study showed most patients with DMG were of 25 years or below age group, whereas the majority of GBMs were of above 50 years age group.…”
Section: Discussionmentioning
confidence: 69%